The National SOM Survey 1986 - SOM Institute, University of Gothenburg (University of Gothenburg, 1987)
In 1986 a series of annual surveys were initiated at the Department of Political Science, Göteborg University. It was called the SOM survey, where SOM stands for Society, Opinions and Mass media. The survey was a result of collaboration between nine different research projects at the department. The questionnaire used was divided into seven subject fields: Mass media, politics and society, energy and nuclear power, Sweden's relation to other countries, residential environment, interests and leisure activities, and social background.

The questions about mass media dealt with how often the respondent watch different television programs, morning paper reading habits, and the occurrence of incorrect and misleading information in mass media.
In the politics and society section you could find questions about the respondent´s confidence in different institutions and groups. The respondents had to give their opinion on a number of proposals occurring in the political debate, they had to place themselves on the political left-right scale, and the political parties and the party leaders on a like-dislike scale. Furthermore the respondents had to answer which party they liked most and how important it is to fulfill different goals in society the next ten years.
Questions concerning energy and nuclear power dealt with the respondent´s attitude toward nuclear power and opinion on the political parties´ energy policy. The respondents had to state how they experienced different risks in connection with the use of nuclear power. There were also questions about confidence in different institutions and groups in regard to giving information about energy and nuclear power. The respondents also had to state if they experienced that they were exposed to any risks in connection with the accident at the nuclear power station in Tjernobyl earlier that year and actions taken to protect themselves against these risks.
In the section about Sweden´s relation to other countries the respondents had to indicate how interested they were in issues concerning foreign policy, aid to developing countries, defence and trade. Furthermore they had to state what they experienced as disturbing for the future and how they believed the military and political situation to be within 10-15 years. They also had to give their opinion on a number of statements concerning foreign policy and defence.
Questions concerning the residential environment dealt with the respondents housing, how long they had lived at the present place and if they had any thoughts of moving elsewhere, and activities in organisations trying to effect the local neighbourhood. The respondents had to indicate if they during the last two years ever tried to influence the local authorities in any local issue or plan concerning the local neighbourhood.
The section about interests and leisure activities included questions on membership in organisations, interest in a number of different issues and activities, and values important for the respondent.
Social background included questions on occupation, union membership, education, vote in 1985, marital status, size of household, income, equipment in household and household´s yearly expense for a number of items.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

1986 startade en serie årliga undersökningar vid statsvetenskapliga institutionen, Göteborgs universitet. Den kallades SOM-undersökningen, där SOM står för samhälle - opinion - massmedia. Undersökningen var ett resultat av ett samarbete mellan nio olika projekt vid institutionen. Det frågeformulär som användes var indelat i sju ämnesområden: massmedier, politik och samhälle, energi och kärnkraft, Sveriges förhållande till omvärlden, boendemiljö, intressen och fritidsaktiviteter samt bakgrundsuppgifter.

Frågor om massmedia behandlar hur ofta respondenten tittat på olika TV-program, läsvanor för morgontidning samt förekomst av felaktiga eller missvisande uppgifter i massmedierna.
Avdelningen med frågor om politik och samhälle innehåller bland annat frågor om respondentens förtroende för hur olika samhällsinstitutioner och grupper sköter sitt arbete. Respondenten fick även ange sin inställning till ett antal förslag som förekommit i den politiska debatten samt placera in sig själv på en politisk vänster-högerskala och de politiska partierna och partiledarna på en gillar-ogillar skala. Därutöver fick respondenterna ange vilket parti man tyckte bäst om och hur viktiga olika samhällsmål kommer att vara för de kommande tio åren.
Frågorna om energi och kärnkraft handlade om respondentens inställning till kärnkraft och åsikt om de politiska partiernas energipolitik. Respondenterna fick även ange hur de upplever olika risker i samband med användning av kärnkraft.
Andra frågor handlade om förtroendet för olika grupper när det gäller information om energi och kärnkraft. Respondenterna fick också ange om de upplevde att de personligen var utsatta för risker i samband med olyckan i kärnkraftverket i Tjernobyl tidigare under året och om man gjort något för att skydda sig mot dessa risker.
I avdelningen om Sveriges relationer till omvärlden fick respondenterna ange hur intresserade de var av utrikespolitik och diplomatiska frågor, biståndspolitik och humanitära frågor, försvarspolitik och militära frågor samt handelspolitik och ekonomiska frågor. Därutöver fick respondenten ange vad man ansåg som mest oroande för framtiden och hur den militära och politiska situationen kommer att vara 10-15 år framåt. Man fick även ange sin ståndpunkt i ett antal förslag som berör utrikespolitik och försvar.
Frågor om boendemiljön handlade om respondentens bostad, hur länge man bott på orten och om man övervägt att flytta till annan ort samt om man deltar i förening eller organisation som försöker påverka närmiljön eller bostadsområdet.
Frågor om intressen och fritidsaktiviteter inkluderar frågor om medlemskap i föreningar, intresse för ett stort antal ämnen och aktiviteter, samt hur viktiga olika värden är.
Bakgrundsavsnittet inkluderar frågor om yrke, fackföreningsmedlemskap, utbildning, parti man röstat på i riksdagsvalet 1985, civilstånd, hushållets storlek, inkomst, utrustning i hushållet samt hushållets årliga utgifter på olika områden.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1986
Riks-SOM 1986
Keywords: developing countries; utvecklingsland; elections; val; housing; boende; mass media; massmedia; defence; försvar; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; culture; kultur; planning; planering; leisure time; fritid; trust; förtroende; political interest; politiskt intresse; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; television news; tv-nyheter; television programmes; tv-program; energy policy; energipolitik; radioactive wastes; radioaktivt avfall; equipment; utrustning; local press; lokalpress; professional ethics; yrkesetik; risk; risk; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; values; värderingar; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap